ANALISIS STARATEGI PERSAINGAN DENGAN PENDEKATAN ANALISIS SWOT MENINGKATKAN LABA UMKM PENJUAL TAHU TEK DI DESA KETAJEN - Muhammad Fikram (LPPM Universitas Bina Bangsa, 2023)
In a business, never escape from competition. Whether it's a large, medium, or even small business, there will definitely be competitors. This is what makes researchers determined to analyze the form of competition and the strategies used to deal with it. Especially in the morning the MSME street vendors who lack knowledge about competition and the analyzes they can use to win the competition. The purpose of the researchers conducting this research is to find out and analyze the impact of competitive advantage on increasing the profits of the UMKM street vendors selling